2017
DOI: 10.1002/jcla.22147
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of procalcitonin, presepsin, and C‐reactive protein in patients with hematological malignancies

Abstract: We conclude that PCT might provide additional information and could be used in combination with other biomarkers to detect infections in patients with hematological malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…The focus of our study was the evaluation of the diagnostic validity of these criteria for the diagnosis of sepsis and the prediction of high risk of in-hospital mortality in a multicentric population of hematological cancer patients. We studied the criteria in analogy to the Sepsis-III study focusing on the criteria and their (bedside) validity, rather than on changes of inflammation markers, which has been studied previously by several groups [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…The focus of our study was the evaluation of the diagnostic validity of these criteria for the diagnosis of sepsis and the prediction of high risk of in-hospital mortality in a multicentric population of hematological cancer patients. We studied the criteria in analogy to the Sepsis-III study focusing on the criteria and their (bedside) validity, rather than on changes of inflammation markers, which has been studied previously by several groups [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have yielded various results. Ebihara et al 16 found that PRE-SEP could be of low diagnostic significance in neutropenic patients, and Koizumi et al 6 showed that the cut-off levels for PRE-SEP in gram-negative bacteremia were higher than the cut-off levels at the onset of febrile neutropenia. Maurice et al 17 identified a positive correlation between the severity of sepsis and PRE-SEP levels, and that PRE-SEP was more specific than CRP in identifying sepsis, while Koh et al 18 reported that PRE-SEP was a more sensitive marker of bacterial infection, than PCT, although the ability of PRE-SEP in differentiating septic shock from other conditions was lower than PCT.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that moderately elevated PCT (1–2.5 ng/mL) could be found in CAP with positive blood culture for Streptococcus pneumoniae mainly in bacterial superinfection after an initial viral episode, possibly reflecting transitory immune impairment ( 33 ). Further, PCT has been shown to strongly correlate with sepsis and septic shock in neutropenic ( 35 , 36 ) and immune-competent patients ( 32 , 37 ). PCT is particularly good in differentiating bacterial from viral meningitis in children ( 38 ) and seems to be useful to rule-in pyelonephritis, but studies on urinary tract infections display a high heterogeneity, which is why PCT cannot be recommended for antibiotic management of urinary tract infections at this point.…”
Section: Procalcitoninmentioning
confidence: 99%